On the Optimal use of Electric Ramjet for Low-orbit Spacecraft. (2017) - Filatyev, A.S.; Yanova, O.V.
Abstract: The problem of the optimal control of spacecraft (SC) with an electric ramjet (ER) to change the orbital parameters is considered. ER uses an air as a fuel. Optimal control is determined by solving the problem on the conditional maximum of the local (at the current point of the orbit) impact of the perturbing acceleration on the functional, assuming the perturbations' smallness compared to gravity. An approximate synthesis of the optimal thrust vector is obtained in view of the power limitation. Parametric investigations of the apogee's changes, depending on the SC with ER parameters, were carried out. The efficiency of the energy and/or fuel accumulation for the implementation of the given orbital flight of SC with ER is shown.